The subtle difference between knowledge and 3D knowledge - Huvila, Isto (Hamburger Journal für Kulturanthropologie (HJK), 2018)
<span style="border: currentColor; color: black; line-height: 107%; font-family: 'Times New Roman',serif; font-size: 11pt; mso-ansi-language: EN-GB; mso-fareast-font-family: 'Arial Unicode MS'; mso-fareast-language: SV; mso-bidi-language: AR-SA;" lang="EN-GB"><span style="border: currentColor; color: black; line-height: 107%; font-family: 'Times New Roman',serif; font-size: 11pt; mso-ansi-language: EN-GB; mso-fareast-font-family: 'Arial Unicode MS'; mso-fareast-language: SV; mso-bidi-language: AR-SA;" lang="EN-GB">This article discusses the implications of attaching three-dimensional artefacts with different labels such as visualisation, model or ‘virtual form’. The research focus is on how this affects the artefact itself, how it is produced and received, and in the end, how the artefact engages in knowledge production, and what kind of knowledge comes out of the process. It is proposed that there is not only a difference between knowledge and ‘three-dimensional’ knowledge but also between knowledge derived from artefacts called by different names. The three-dimensional artefacts are intermediaries or boundary objects between the past and the present, and the makers and users of these objects. Taking the differences in names and how they are linked to epistemological differences seriously and making them visible is argued to be a key to a more reflexive and productive making and use of three-dimensional artefacts.